PERAN METODE PEMBELAJARAN TAR-Q DALAM MENINGKATKAN KUALITAS BACAAN AL-QUR’AN SISWA KELAS 7 SMP IT IBADURROHMAN TASIKMALAYA - Muhammad Nabhan Taqiyuddin; Zainul Abidin, Muhamad; Abidin, Zainul (Program Studi Pendidikan Agama Islam, 2025)
This study aims to examine the effectiveness of the Tar-Q learning method in improving the Qur’an recitation quality of seventh-grade students at SMP IT Ibadurrohman Tasikmalaya. The Tar-Q method emphasizes gradual, systematic mastery of recitation through direct practice under teacher guidance. This research employs a classroom action research approach with a qualitative descriptive method. Data were collected through observation, interviews, and documentation, involving the school principal, teachers, and selected students as subjects. Data analysis was conducted through data reduction, presentation, and conclusion drawing. The results indicate that the Tar-Q method significantly enhances students’ tilawah skills, as reflected in increased learning achievement scores and greater student engagement in the learning process. However, some challenges were identified, including limited guidance from the central Tar-Q institution and less systematic material in the Tar-Q book, which complicated the learning process for both teachers and students. Overall, the Tar-Q method is effective in improving Qur’an recitation quality in terms of both technical accuracy and learning attitudes. With competent teachers, proper instructional systems, and improvements in material and guidance, this method has strong potential for wider application in Qur’an learning in schools.